INTERVENSI PEKERJAAN SOSIAL TERHADAP ANAK PENDERITA TRAUMA KORBAN KONFLIK SOSIAL: PENDEKATAN BIO-PSIKHO-SOSIAL-SPIRITUAL (STUDI KASUS PADA YAYASAN “PNIEL” DI TANGERANG) - Salakory, David Marthen (Istek Widuri Jakarta, 2017)
Trauma can be caused by certain conditions or incidents that occur in someone’s life, family, as well as in the society. One of the cases that drives a child into traumatic experience is bacause of the social conflict, such as war. In addition, trauma can also happen due to the natural disasters and violences. Trauma may refers to painful and shocking experiences that that cause a state of human stress.Furthermore, trauma can be also meant as physical and psychological or mental injuries. Post Traumatic Stress is a stress state that experienced after trauma. This condition may also cause someone’s disorder, which is called Post Traumatic Stress Disorder. An accomplishment in treatment and recovery of trauma may happen if a client is able to integrate his traumatic experience as a reality of life.